The Effect of Enterprise Resources Planning Implementation on Supply Chain Management on Micro, Small and Medium Enterprises Performance - Putri, Meisyah; Aprillian, Harries; Rupianti, Reni (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
Micro, Small and Medium Enterprises play a very large role in the Indonesian economy and indirectly support the Indonesian economy. Supply Chain Management is the process of managing goods, information, and finance from suppliers to end consumers. Enterprise Resource Planning is a system used to manage and automate various business processes in organizations to improve efficiency and data accuracy. This research was made to find out and analyze the application of Supply Chain Management based on Enterprise Resource Planning for Micro, Small and Medium Enterprises. This research uses qualitative methods in the form of journal articles and related books, as well as interviews and observations with several Micro, Small and Medium Enterprises owners in Malang City, East Java, Indonesia. The results of the study show and support that the collaboration of Supply Chain Management and Enterprise Resource Planning applied by several Micro, Small and Medium Enterprises owners has a positive impact on business actors, especially on business development until now consistently producing and distributing products on target.